Moderating Effect of Environmental Quality on the Relationship Between Trade Openness and Health Expenditure in Sub-Saharan African Countries - Ekwebe, Awa’oma Abaimbi; Angelus, Efeutlancha Forji (Finance & Economics Review, 2025)
Purpose: The main objective of this study is to investigate the moderating effect of environmental quality on the relationship between trade openness and health expenditure in sub-Saharan African countries. Methods: This research utilizes panel data from 41 member countries of sub-Saharan Africa, covering the period from 1996 to 2020. Data was sourced from the World Development Indicators (WDI). The econometric analysis employs the Generalized Method of Moments (GMM) technique to address endogeneity issues in panel data. Results: The findings reveal a significant positive relationship between trade openness and health expenditure in sub-Saharan African countries. Specifically, a 1% increase in trade openness corresponds to a 582.4-point increase in health expenditures. However, the study also indicates that trade openness negatively impacts environmental quality, as a unit increase in trade openness leads to a decline in environmental quality. This degradation has adverse health outcomes, contributing to increased health spending due to increased incidences of cardiovascular diseases, eye defects, and respiratory tract infections. The study finds that Gross Domestic Product (GDP) per capita negatively affects health expenditure, with a 1% increase resulting in a 0.1843-point decrease. Conversely, population growth positively influences health expenditure, where a 1% increase leads to a 0.1099-point rise in health spending. Industrialization has also been found to have a positive and statistically significant effect on health expenditure at the 5% level, although it contributes to environmental degradation, further impacting human health. Implications: This study’s theoretical implications enhance our understanding of the interconnections between trade, health expenditures, and environmental quality.